Properties of mortar using cubes, prism halves, and cylinder specimens - Parsekian, G. A.; Fonseca, F. S.; Pinheiro, G. L.; Camacho, J. S. [UNESP] (American Concrete Institute, 2014)
The compressive strength of quasi-brittle materials, such as mortar, is affected by the shape and size of specimens tested. The Brazilian standards recently changed the method and the shape of the specimens used to determine the strength of mortar. An experimental program was devised to determine the relationship of mortar properties obtained from testing the old shape (prism halves or cube) and the new shape (cylinder) specimens. Mortar batches were prepared with a lime-cement ratio from 0.25 to 3 and a sandcement ratio from 2 to 12. Both fresh and hardened mortar properties were determined. The analysis of the results yielded correlations between the strengths of the different specimens. For mortar strength between 4 and 12 MPa (580 and 1740 psi), the strength of cylindrical specimens was 30% lower than that of prism halves specimens; for mortar strength less than 4 MPa (580 psi), the reduction varied from 37 to 49%; while for mortar strength greater than 12 MPa (1740 psi), the reduction varied from 1 to 26%. A relationship was also developed to help engineers proportion mortar based on different percentages of lime and sand. Copyright © 2014.
Keywords: Compressive strength; Cube specimens; Cylinder specimens; Flexural strength; Mortar; Mortar properties; Prisms; Specimen shape effect